Hardening Linux - Turnbull, James (Apress : Imprint: Apress, 2005)
"Hardening" is the process of protecting a system and its applications against unknown threats. Hardening Linux identifies many of the risks of running Linux hosts and applications and provides practical examples and methods to minimize those risks. The book is written for Linux/UNIX administrators who do not necessarily have in-depth knowledge of security but need to know how to secure their networks.